Strengthening and evaluating the preventing malnutrition in children under 2 years of age approach: Guatemala follow-up report - Heckert, Jessica; Leroy, Jef L.; Bliznashka, Lilia; Olney, Deanna K.; Richter, Susan (FHI 360; FANTA, 2018)
This report presents the findings from the impact evaluation of Programa Comunitario Materno Infantil de Diversificación Alimentaria (PROCOMIDA) (Community Maternal and Child Food Diversification Program), a Preventing Malnutrition in Children under Two Years of Age (PM2A) program that was implemented in Alta Verapaz region, Guatemala, from 2011 to 2015. The report assesses the impact of PROCOMIDA on mothers and their children at key time points from early gestation until the child reached 24 months old.